Liberia's coastal erosion vulnerability and LULC change analysis: Post-civil war and Ebola epidemic. (December 2018) - Awange, J.L.; Saleem, A.; Konneh, S.S.; Goncalves, R.M.; Kiema, J.B.K.; Hu, K.X.
Abstract: In most developing countries, data for coastal change and vulnerability assessment is hard to come by due, e.g., to data inaccessibility or incomplete dataset. In some countries, e.g., Liberia, a country that was ravaged by civil war and Ebola epidemic, such extraneous factors prevent direct observations, i.e., "boots on the ground". This study examines temporal changes in land use/land cover (LULC), coastline changes, and coastal vulnerability to erosion and their effects on Liberia over a period of 29 years (1986–2015). The results from the post-classification change detection analysis using Landsat data (validated by moderate resolution Sentinel-2 product) show that bare land and sediment classes decreased over the entire study period by 5.07% and 0.06%, respectively. Water, vegetation, and residential classes are found to have increased during the 29 years of evaluation by 0.41%, 3.29% and 1.43%, respectively. Vegetation cover during the post-civil war era (2002–2015), however, reduced by about 0.31%. Furthermore, the results for the coastal analysis indicate more erosion during the period 1998–2002, i.e., the post-civil war period. The results also show an increase in residential areas possibly due to population growth, especially in the most populated areas such as Monrovia, the capital city. Highlights: Landsat suffice for Liberia's coastal study while Sentinel-2 has future potential. Liberia experienced more erosion than accretion in the period 1986–2015. Both civil war and Ebola epidemic influenced land use/land cover changes. Climate change also plays a significant role in Liberia's coastal vulnerability.